Multi-omics elucidation of yellow aril coloration in litchi (Litchi chinensis Sonn.) cultivar ‘Jianjianghongnuo’: coordinated downregulation of flavonoid and carotenoid biosynthetic pathways drives pigment dynamics - Pan, Mianqiao; Wang, Han; Ning, Zhenchen; Yu, Xiaoqian; Liu, Hecheng; Huang, Xiaomei; Chen, Houbin; Su, Zuanxian (Frontiers in Plant Science, 2025)
Litchi (Litchi chinensis Sonn.) arils are predominantly white or cream-colored, with yellow-pigmented cultivars being rare and poorly characterized. The ‘JJHN’ cultivar exhibits a distinctive yellow aril that progressively attenuation during fruit development, providing an ideal model to investigate the biochemical and molecular basis of yellow pigmentation in litchi. In this study, we integrated phenotypic evaluation, widely targeted and carotenoid-targeted metabolomics, and transcriptomic analyses at ‘JJHN’ arils across fruit development. The color shift from orange-yellow to pale yellow during ripening, as indicated by declining CIE b* values, was accompanied by significant reductions in total flavonoid and carotenoid contents. Widely targeted metabolomics profiling revealed that aurones (e.g., aureusidin 4,6-diglucoside) and chalcones (e.g., naringin chalcone) were the primary yellow pigments. Targeted carotenoid analysis identified violaxanthin as the predominant carotenoid during early development, accounting for 62.4% of total carotenoids at stage Y2, but decreasing sharply and becoming undetectable at maturity. Transcriptomic data showed coordinated downregulation of structural genes involved in flavonoid (e.g., CHS, CHR, CHI) and carotenoid (e.g., ZEP, AAO3) biosynthesis, aligning with the observed pigment depletion. Weighted gene co-expression network analysis (WGCNA) identified a “turquoise” module positively correlated with flavonoid content, comprising transcription factors from MYB, bHLH, bZIP, NAC, and DOF families that possessed predicted binding sites in pigment-related gene promoters. Collectively, these findings demonstrate that the yellow aril phenotype of cv. ‘JJHN’ is regulated by a dual pigment system—aurones/chalcones and violaxanthin—whose developmental depletion is transcriptionally controlled by a complex TF network. This study provides novel insights into the regulation of fruit pigmentation and lays a foundation for breeding litchi cultivars with yellow arils.